Effects of computer-assisted cognitive behavioral therapy on anxiety in patients undergoing functional endoscopic sinus surgery: an exploratory fNIRS study of prefrontal hemodynamic functions - Yang, Yang; Zhang, Haibin; Hu, Chen; Tong, Yuping (Frontiers in Psychiatry, 2026)
IntroductionWe investigated prefrontal cortex (PFC) activation in patients undergoing functional endoscopic sinus surgery (FESS) who presented with anxiety, and we evaluated the effect of a computer-assisted cognitive behavioral therapy (cCBT) intervention using functional near-infrared spectroscopy (fNIRS).MethodsSixty patients scheduled for FESS were randomly assigned to either the active control (AC) group (n = 30) that received health education or the cCBT group (n = 30) that received cCBT. Prefrontal hemodynamic responses were assessed using fNIRS during the performance of the verbal fluency task (VFT). Levels of anxiety, depression, and insomnia were measured at multiple perioperative time points.ResultsThe cCBT group exhibited a significantly greater number of activated channels than the AC group (37 vs. 27, p = 0.004) and higher changes in oxygenated hemoglobin (Δoxy-Hb) in specific channels (Channels 15, 23, 26, and 35; p < 0.05). Oxygenated hemoglobin (oxy-Hb) levels in Channel 41 were negatively correlated with state anxiety scores (p = 0.008), whereas those in Channel 42 were positively correlated with insomnia severity (p = 0.038) at baseline. Changes in the activation of Channel 34 and Channel 3 were correlated with the alleviation of anxiety and insomnia symptoms, respectively.DiscussionAnxiety in patients undergoing FESS was associated with reduced PFC activation during the VFT. The cCBT intervention improved clinical symptoms and enhanced PFC hemodynamic function. cCBT serves as an effective non-pharmacological intervention for mitigating anxiety and insomnia in this patient population.Clinical Trial RegistrationClinicalTrials.gov, identifier ChiCTR2500113914.